ASAS PENCEMAR MEMBAYAR (POLLUTER PAYS PRINCIPLE) : BENTUK PERTANGGUNGJAWABAN HUKUM PELAKU USAHA YANG MELANGGAR BAKU MUTU AIR LIMBAH - Muhammad Khalid Ali; Evi dwi Hastri; AA Muhammad Insany Rachman (LPPM Universitas Nias Raya, 2023)
This study aims to analyze how the form of legal responsibility of business actors by applying the polluter pays principle as a problem solving achieves success in resolving environmental disputes that violate wastewater quality standards. This type of research uses normative legal research. The problem approach used is a statute approach with a method of analyzing legal materials that relefan with legal issues in a deductive and descriptive qualitative manner. The novelty of this research shows that the form of legal responsibility of business actors facing environmental disputes that violate wastewater quality standards is not always resolved with criminal sanctions contained in Article 100 of the UUPPLH. However, it can be realized by applying the Polluter Pays Principle which requires business actors other than paying compensation, polluters and/or environmental destroyers are also burdened by judges to take certain legal actions. Therefore, the responsibility of business actors for environmental pollution can be carried out criminal, civil and administrative responsibilities.